C.1 - Pant, J. C. (New Delhi, 2010)
This autobiographical narration describes the manner in which the Guru skillfully steered and guided the personality of the disciple, and the description of this impact on the latter, throws a volume of light on the essential persona of the former.
Keywords: Civil Servant-Biography